HUBUNGAN SIMULTAN KEPEMILIKAN MANAJERIAL, RISIKO, KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN DAN KINERJA KEUANGAN PERUSAHAAN TERBUKA DI INDONESIA - S. Budi Prasetyo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
Objectives of this research are to know simultaneous relationship between managerial ownership, risk, debt policy, and company financial performance; and to find empirical evidences that control mechanism through stock ownership, dividend, and debt can reduce agency problem so that reducing agency cost in public companies in Indonesia. Samples of this research are 149 publicly owned companies listed in Jakarta Stock Exchange (JSX) in 2000-2004 which determined by judgment sampling. Two-Stage Least Square (2-SLS) is used to analyze the samples. This research shows that managerial ownership has significant influence to debt policy and there is a negative causal relationship between managerial ownership and debt policy. There is a substitution relationship between managerial ownership and dividend policy meaning that there is a significant negative causal relationship between managerial ownership and dividend policy; and between dividend policy and managerial ownership. Furthermore, there is also a substitution relationship between debt policy and dividend policy meaning that there is a significant negative causal relationship between debt policy and dividend policy; and between dividend policy and debt policy. Risk is a significant determinant factor and has negative influence to managerial ownership, whilst managerial ownership also a significant determinant factor and has negative influence to risk. Company’s financial performance has a significant positive influence to debt policy, while debt policy has a significant positive influence to company’s financial performance.